2015
DOI: 10.1158/2326-6066.cir-15-0088
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing to Predict Neoantigens in Melanoma

Abstract: The ability to use circulating peripheral blood cells and matched tumor sequencing data as a basis for neoantigen prediction has exciting possibilities for application in the personalized treatment of cancer patients. We have used a high-throughput screening approach, combining whole-exome sequence data, mRNA microarrays, and publicly available epitope prediction algorithm output to identify mutated proteins processed and displayed by patient tumors and recognized by circulating immune cells. Matched autologou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
2
46
0
2
Order By: Relevance
“…This then results in epitope spreading to other antigens, including mutated ones, which are currently considered critical rejection antigens. Interestingly, the standard DC vaccine as used in our study (i.e., cocktail-matured monocytederived DCs), but loaded with dying autologous tumor cells in 2 small trials (70,71), also resulted in longterm survival and, as recently shown in neo-epitope-specific T cells (81), underscoring the immunogenicity of this simple yet highly standardized nontoxic DC vaccine.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 62%
“…This then results in epitope spreading to other antigens, including mutated ones, which are currently considered critical rejection antigens. Interestingly, the standard DC vaccine as used in our study (i.e., cocktail-matured monocytederived DCs), but loaded with dying autologous tumor cells in 2 small trials (70,71), also resulted in longterm survival and, as recently shown in neo-epitope-specific T cells (81), underscoring the immunogenicity of this simple yet highly standardized nontoxic DC vaccine.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 62%
“…To identify neoantigens, sequencing only the exome can dramatically reduce the cost and minimize the complexity of data analysis [19]. Now, whole-exome sequencing (WES) combined with RNA sequencing (RNA-Seq) and epitope prediction method was proved to be an efficient approach [3,20].…”
Section: Next Generation Sequencing Based Methodsmentioning
confidence: 99%
“…So identification of neoantigen is a pivotal work in both fundamental studies and clinical immunotherapies. With the fast development of next generation sequencing (NGS) and mass spectrometry technology, neoantigens can be indirectly predicted from genome research by generating high-throughput sequencing data or directly identified by LC-MS/MS in an unbiased manner [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenicity of the DC vaccine was shown for shared antigens as well as neoepitopes. Despite the current dogma that a high mutational load enhances the chances for a good prognosis, in patients vaccinated with DCs loaded with autologous tumor, melanoma-reactive T cells recognized not only neoantigens 18,19 . In order to not restrict immune responses to next generation sequencing (NGS)-predicted neoepitopes or defined shared tumor antigens but take advantage of the total antigenic repertoire, DCs were transfected by the Erlangen group with PCR-amplified autologous total tumor RNA and are currently being tested in a randomized, multicenter phase III clinical trial of monosomy 3-positive uveal melanoma (NCT01983748), a highly metastatic disease with no effective standard therapy, few mutations and high resistance to checkpoint blockade.…”
Section: Introductionmentioning
confidence: 94%